The Differences Entrenched in Indian Constitution and American Constitution – A Comparative Interpretation: A Comparative Analysis of Constitutional Dimensions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In an effort to recognised and analyse legal texts written in the developing world, many of us trained in the developed world have questions to the degree cultural disparities can impact how we treat the role of interpretation. Before we get to grips with the text at question, we must recognised the suitability to use our usual interpretive methods and the usual interpretation of legal requirements in order to render material produced in a social and political sense which is drastically different. The position of meaning is of special significance because the text of the developed world was focused on an American model. The above situation motivates an unimaginative argument in our commonly-placed understanding and the unimaginative assumption ties the legal terminology of a one-dimensional connotation to which we bind it. As a result, the related qualitative variations could not be taken into consideration. The present article discusses the complexity of the constitutional dimensions and their meaning.